Method for surface treatment of Ti and Al under same conditions to bond polymers and metals

By adjusting the surface treatment parameters and steps, Ti and Al are subjected to surface treatment under the same conditions to form a porous oxide coating, which solves the problem that different types of metals cannot be treated simultaneously in the prior art, and improves the bonding strength between polymer and metal.

CN119553331APending Publication Date: 2025-03-04GEO NATION CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411219938.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2024-09-02
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art cannot surface treatment of different types of Ti and Al under the same conditions, resulting in the inability to bond simultaneously, increasing time and cost.

Method used

By adjusting the surface treatment parameters, the surface treatment of Ti and Al under the same conditions is carried out to form a porous oxide coating by degreasing, etching, decontamination, activation, anodizing and drying.

Benefits of technology

Ti and Al are surface treated under the same conditions to form a porous oxide coating, which improves the bonding strength between the polymer and Ti or Al, and achieves the same or better bonding effect as under the respective optimal conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553331A_ABST
    Figure CN119553331A_ABST
Patent Text Reader

Abstract

The present invention provides a method of surface treating a metal under the same conditions to bond a polymer and the metal, involving the bonding of the polymer with Ti or polymer with Al. The method comprises a degreasing step in which contaminants are removed from the metal surface using a degreasing detergent; a first etching step in which the metal surface is etched with an alkaline solution; a decontaminating step in which stains are removed from the metal surface; an activation step in which the metal surface is etched with a strong acid solution; an anodic oxidation step in which a porous structure is formed on the activated metal surface; and a drying step, in which the anodized metal surface is dried.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for bonding a polymer and a metal by surface treating a metal under the same conditions, and more particularly to a method for forming a porous oxide coating on the surfaces of completely different types of Ti and Al by surface treating the metal under the same treatment conditions. Background Art

[0002] Polymer-Ti joints and polymer-Al joints are widely used in electronic components and smartphones that need to be waterproof. However, the surface treatment process conditions of Ti and Al are different from each other, making it impossible to process them at the same time. Therefore, it is necessary to change the process conditions of each material, resulting in separate operations for Ti (Patent Document 1, Japanese Unexamined Patent Application Publication No. 2019-048407) and Al (Patent Document 2, Japanese Patent No. 4600701), which brings problems in time and cost. Especially when the number of parts is small, a lot of time and money is wasted.

[0003] To solve the above problems, a method was developed in which Ti and Al can be surface treated under the same conditions by adjusting the surface treatment parameters (e.g., solution, concentration, temperature, time, and current) to a single set of surface treatment conditions.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2019-048407

[0007] Patent Document 2: Japanese Patent No. 4600701 Summary of the invention

[0008] Technical issues

[0009] In order to solve the above-mentioned problems, the present invention aims to provide a method of surface-treating Ti and Al under the same conditions, although they are completely different types of metals, to form porous oxide coatings on their surfaces.

[0010] Technical solutions to the problem

[0011] According to the present invention, a method for surface treating a metal under the same conditions to bond a polymer to the metal involves bonding a polymer to Ti or a polymer to Al, comprising the following steps:

[0012] a degreasing step, in which a degreasing detergent is used to remove contaminants from the metal surface;

[0013] A first etching step, wherein the metal surface is etched with an alkaline solution;

[0014] a decontamination step, wherein contaminants are removed from the metal surface;

[0015] an activation step, in which the metal surface is etched with a strong acid solution;

[0016] an anodizing step, wherein a porous structure is formed on the activated metal surface; and

[0017] The drying step is used to dry the anodized metal surface.

[0018] The anodizing step is carried out at a temperature of 30-50°C and 1.0-2.55A / dm 2 The reaction is carried out for 300-1200 seconds using a mixed acidic solution with a pH value of 4.5-5.5 at a current density of , wherein the mixed acidic solution includes one or more of sulfuric acid (concentration 1-3 g / L), phosphoric acid (concentration 2-7 g / L), chromic acid (concentration 1-5 g / L), oxalic acid (concentration 1-5 g / L) and hydrofluoric acid (concentration 0.5-2 g / L), and one or more of sodium sulfate (concentration 5-10 g / L), phosphate (concentration 1-5 g / L) and oxalate (concentration 1-3 g / L), and triazine thiol derivatives and salts thereof (concentration 0.01-0.10 g / L) are added as additives.

[0019] The additive used in the anodizing step is one of the following triazine thiol derivatives and salts thereof:

[0020] 1,3,5-Triazine-2,4,6-trithiol (TT),

[0021] 1,3,5-Triazine-2,4,6-trithiol monosodium salt (TTN),

[0022] 1,3,5-Triazine-2,4,6-trithiol triethanolamine salt (F-TEA),

[0023] 6-anilino-1,3,5-triazine-2,4-dithiol (AF),

[0024] 6-anilino-1,3,5-triazine-2,4-dithiol monosodium salt (AFN),

[0025] 6-Dibutylamino-1,3,5-triazine-2,4-dithiol (DB),

[0026] 6-Dibutylamino-1,3,5-triazine-2,4-dithiol monosodium salt (DBN),

[0027] 6-Diallylamino-1,3,5-triazine-2,4-dithiol (DA),

[0028] 6-Diallylamino-1,3,5-triazine-2,4-dithiol monosodium salt (DAN),

[0029] 1,3,5-Triazine-2,4,6-trithiol di(tetrabutylammonium) salt (F2A),

[0030] 6-Dibutylamino-1,3,5-triazine-2,4-dithiol tetrabutylammonium salt (DBA),

[0031] 6-Dioctyl-1,3,5-triazine-2,4-dithiol (DO),

[0032] 6-Dioctyl-1,3,5-triazine-2,4-dithiol monosodium salt (DON),

[0033] 6-Dilauroylamino-1,3,5-triazine-2,4-dithiol (DL),

[0034] 6-Dilauroylamino-1,3,5-triazine-2,4-dithiol monosodium salt (DLN),

[0035] 6-Stearylamino-1,3,5-triazine-2,4-dithiol (ST),

[0036] 6-Stearylamino-1,3,5-triazine-2,4-dithiol monopotassium salt (STK),

[0037] 6-oleylamino-1,3,5-triazine-2,4-dithiol (DL), and

[0038] 6-Oleamido-1,3,5-triazine-2,4-dithiol monopotassium salt (OLK).

[0039] Beneficial effects of the present invention

[0040] According to the present invention, completely different types of metals Ti and Al are surface treated under the same conditions to form porous oxide coatings on their surfaces. The bonding strength between Ti and the polymer and between Al and the polymer is then measured. The tensile strength, the tensile strength after thermal shock, and the tensile strength after exposure to constant temperature and humidity show bonding strengths comparable to or better than those obtained when Ti and Al are surface treated under their respective optimal conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 A flow chart showing a method of surface treating a metal for bonding a polymer and a metal under the same conditions, wherein it involves bonding of a polymer to Ti or a polymer to Al.

[0042] Figure 2(a) shows a plan view of the shape of a Ti or Al metal member used for a tensile test specimen.

[0043] Figure 2 (b) shows a side view of the shape of the Ti or Al metal member used for the tensile test specimen.

[0044] Figure 2 (c) shows a schematic diagram of a combination of a Ti or Al metal component and a polymer, wherein the combination is a specimen for a tensile test. The polymer is injected from a gate and bonded to the Ti or Al metal component.

[0045] Figure 3 (a) Photograph showing the surface morphology of the porous oxide coating on Ti (magnification: 10 5 times), which is very suitable for the surface treatment according to the present invention.

[0046] Figure 3 (b) Photograph showing the surface morphology of the porous oxide coating on Al (magnification: 10 5 times), which is very suitable for the surface treatment according to the present invention. DETAILED DESCRIPTION

[0047] The following describes a method of the present invention for surface treating a metal to bond a polymer and a metal under the same conditions, such as Figure 1 shown.

[0048] According to one embodiment of the present invention, a method for surface treating a metal under the same conditions to bond a polymer and a metal involves bonding a polymer to Ti or a polymer to Al, comprising the following steps:

[0049] (a) a degreasing step, in which contaminants are removed from the metal surface using a degreasing detergent;

[0050] (b) a water rinsing step, wherein the metal surface is rinsed with water after the degreasing step;

[0051] (c) a first etching step, wherein the metal surface is etched with an alkaline solution;

[0052] (d) a water rinsing step, wherein the metal surface is rinsed with water after undergoing the first etching step;

[0053] (e) a decontamination step, wherein contaminants are removed from the metal surface;

[0054] (f) a water rinsing step, wherein the metal surface after the decontamination step is rinsed with water;

[0055] (g) an activation step, wherein the metal surface is etched a second time with a strong acid solution;

[0056] (h) a water rinsing step, wherein the metal surface is rinsed with water after undergoing the activation step;

[0057] (i) an anodizing step, wherein a porous structure is formed on the activated metal surface;

[0058] (j) a water rinsing step, wherein the metal surface is rinsed with water after undergoing the anodizing step; and

[0059] (k) A drying step, in which water is removed from the metal surface after rinsing with water.

[0060] In step (a), contaminants on the metal surface are removed by washing with an aluminum degreasing detergent or by immersing the metal in a water-soluble organic solvent at 60° C. for 3 minutes.

[0061] In step (b), the metal surface is rinsed with water to remove the water-soluble organic solvent.

[0062] In step (c), the metal surface is etched at 40° C. for 2 minutes using an alkaline series metal etchant, which includes KOH, alkali metal hydroxide, soda ash ( Anhydrous sodium carbonate) and ammonia. This process forms etching marks on the metal surface and roughens the surface.

[0063] In step (d), after the first etching step, the metal surface is rinsed with water to remove the alkaline solution.

[0064] In step (e), stains on the metal surface are removed using a detergent at 25° C. for 1 minute, the detergent including nitric acid, sulfuric acid, hydrofluoric acid, acidic ammonium fluoride, sodium fluoride and hydrogen peroxide.

[0065] In step (f), after the decontamination step, the metal surface is rinsed with water to remove any residual decontaminant.

[0066] In step (g), the metal surface is subjected to a second etching in a strong acid solution such as sulfuric acid, acetic acid, organic acid or hydrofluoric acid at 40° C. for 30 seconds as an activation treatment.

[0067] In step (h), the activated metal surface is rinsed with water.

[0068] In step (i), a mixed acidic solution with a pH value of 4.5-5.5 is used at 30-50°C and a temperature of 1.0-2.5 A / dm 2The anodizing treatment is carried out for 300-1200 seconds at a current density of . The solution includes one or more of the following acids: sulfuric acid (concentration 1-3 g / L), phosphoric acid (concentration 2-7 g / L), chromic acid (concentration 1-5 g / L), oxalic acid (concentration 1-5 g / L) and hydrofluoric acid (concentration 0.5-2 g / L). The solution also includes one or more of the following salts: sodium sulfate (concentration 5-10 g / L), phosphate (concentration 1-5 g / L) and oxalate (concentration 1-3 g / L). Triazine dithiol derivatives and their salts (concentration 0.01-0.10 g / L) are used as additives. The treatment forms an oxide coating with many pores on the etched metal surface, and the porous coating and the pores are impregnated with triazine dithiol derivatives and their salts. This increases the bonding strength between the metal and the polymer, thereby improving the adhesion.

[0069] In step (i), the additive used is one of the following triazine thiol derivatives and salts thereof:

[0070] 1,3,5-Triazine-2,4,6-trithiol (TT),

[0071] 1,3,5-Triazine-2,4,6-trithiol monosodium salt (TTN),

[0072] 1,3,5-Triazine-2,4,6-trithiol triethanolamine salt (F-TEA),

[0073] 6-anilino-1,3,5-triazine-2,4-dithiol (AF),

[0074] 6-anilino-1,3,5-triazine-2,4-dithiol monosodium salt (AFN),

[0075] 6-Dibutylamino-1,3,5-triazine-2,4-dithiol (DB),

[0076] 6-Dibutylamino-1,3,5-triazine-2,4-dithiol monosodium salt (DBN),

[0077] 6-Diallylamino-1,3,5-triazine-2,4-dithiol (DA),

[0078] 6-Diallylamino-1,3,5-triazine-2,4-dithiol monosodium salt (DAN),

[0079] 1,3,5-Triazine-2,4,6-trithiol di(tetrabutylammonium) salt (F2A),

[0080] 6-Dibutylamino-1,3,5-triazine-2,4-dithiol tetrabutylammonium salt (DBA),

[0081] 6-Dioctyl-1,3,5-triazine-2,4-dithiol (DO),

[0082] 6-Dioctyl-1,3,5-triazine-2,4-dithiol monosodium salt (DON),

[0083] 6-Dilauroylamino-1,3,5-triazine-2,4-dithiol (DL),

[0084] 6-Dilauroylamino-1,3,5-triazine-2,4-dithiol monosodium salt (DLN),

[0085] 6-Stearylamino-1,3,5-triazine-2,4-dithiol (ST),

[0086] 6-Stearylamino-1,3,5-triazine-2,4-dithiol monopotassium salt (STK),

[0087] 6-oleylamino-1,3,5-triazine-2,4-dithiol (DL), and

[0088] 6-Oleamido-1,3,5-triazine-2,4-dithiol monopotassium salt (OLK).

[0089] In step (j), after anodizing, the metal surface was rinsed with water at 60° C. for 30 seconds.

[0090] In step (k), the rinsed metal surface is dried with hot air at 80° C. for 5 minutes.

[0091] The polymer that can be used in the present invention is a thermoplastic resin such as polybutylene terephthalate (PBT), polyphenylene sulfide (PPS), polyphthalamide (PPA), polyethylene terephthalate (PET), polycarbonate (PC), polyimide (PI), polyaryletherketone (PAEK), and polyetheretherketone (PEEK), etc. These are not limited to the above examples, and various other polymer resins can also be applied.

[0092] The polymer used in the experimental samples was polybutylene terephthalate (PBT), specifically WF008NXQ 7N1A4352 from SABIC.

[0093] The surface treatment processes for producing a combination of polymer and Ti or Al are compared between conventional examples and the present invention. Table 1 summarizes the process of conventional example 1 for Ti, Table 2 summarizes the process of conventional example 2 for Al, and Table 3 summarizes the surface treatment process of the present invention.

[0094] Table 1

[0095]

[0096]

[0097] In the conventional example 1 of Ti in Table 1, in the anodizing step of process number 7, a sulfuric acid solution (concentration 180 g / L) was used at 60°C with a flow rate of 0.55 A / dm 2 The anodizing treatment was carried out for 900 seconds at a current density of , wherein the additive 1,3,5-triazine-2,4,6-trithiol (concentration 0.01-0.10 g / L) was added to the sulfuric acid solution.

[0098] Table 2

[0099]

[0100]

[0101] In the conventional example 2 of Al in Table 2, in the anodizing step of process number 7, a mixed alkaline solution of caustic soda (concentration 30 g / L), sodium phosphate (concentration 3 g / L) and phosphoric acid (concentration 10 g / L) was used at 50°C with a flow rate of 5.0 A / dm 2 The anodizing treatment was carried out for 900 seconds at a current density of , wherein the additive 1,3,5-triazine-2,4,6-trithiol (concentration 0.01-0.10 g / L) was added to the mixed alkaline solution.

[0102] Table 3

[0103]

[0104]

[0105] In the example of the present invention shown in Table 3, in the anodizing step of process number 9, a mixed acid solution with a pH of 4-6 was used at 30-50°C and a flow rate of 1.0-2.5 A / dm 2 The anodizing treatment is carried out for 300-1200 seconds at a current density of , wherein the mixed acidic solution includes sulfuric acid (concentration 1-30 g / L) and sodium sulfate (concentration 5-15 g / L), and 1,3,5-triazine-2,4,6-trithiol (concentration 0.01-0.10 g / L) is added thereto.

[0106] Thus, samples of Conventional Examples 1 and 2, Inventive Examples 1 to 15, and Comparative Examples 1 to 7 were prepared under the conditions shown in the following table.

[0107] Table 4

[0108]

[0109]

[0110]

[0111] The abbreviations used in Table 4 are:

[0112] Inv.Ex.: Example of the present invention

[0113] Comp.Ex.: Comparative Example

[0114] Conv.Ex.: Conventional example

[0115] ·ST: Standard (normal conditions)

[0116] Figure 2 (a) is a plan view of a metal member used as a tensile test specimen in Conventional Examples 1 and 2, Inventive Examples 1 to 15, and Comparative Examples 1 to 7. The specimen was made of Ti (grade 5) or Al (Al 6061) and had dimensions of 12 mm in width, 40 mm in length, and 3 mm in thickness. Figure 2 (c) shows a combination in which the polymer is bonded to each sample of Ti (grade 5) or Al (Al 6061). The polymer with a width of 12 mm, a length of 42 mm, and a thickness of 3 mm was vertically injected through the gate and bonded to Ti or Al.

[0117] Figure 2 (c) shows a polymer-Ti or polymer-Al combination 3, in which the polymer component 2 is integrally formed with the Ti or Al metal component 1 by injection molding. The injection molding process includes first loading the Ti or Al metal component 1 into a mold, and then pressing the polymer (thermoplastic resin) into the joint area of ​​the mold so that the Ti or Al metal component 1 and the polymer component 2 are integrally formed. As the thermoplastic resin, polybutylene terephthalate (PBT) or polyphenylene sulfide (PPS) can be used. The contact area between the Ti or Al metal component 1 and the polymer component 2 is about 36mm 2 (12mm×3mm) because they are connected linearly. Figure 2 The polymer-Ti or polymer-Al combination 3 shown in (c) was used as a specimen for tensile testing to investigate the bonding strength.

[0118] Figure 3 (a) and 3(b) show the surface morphology of porous oxide coatings suitable for surface treatment according to the present invention. Figure 3 (a) shows the surface morphology of the porous oxide coating on Ti, Figure 3 (b) shows the surface morphology of the porous oxide coating on Al.

[0119] It can be seen that an oxide coating having many pores is formed on the metal surface.

[0120] [Experimental Example 1]

[0121] <Tensile test>

[0122] Test machine: HZ-1003A produced by MMS TECH

[0123] Test method:

[0124] 1) Prepare tensile specimens.

[0125] 2) Secure each specimen to the grip of the tensile testing machine.

[0126] 3) Perform tensile test at a speed of 5 mm / min.

[0127] 4) Record the value of the point where the injected polymer separates from the metal.

[0128] [Experimental Example 2]

[0129] <Tensile test after thermal shock>

[0130] Test machine: SUKSAN SE-TS-05

[0131] Test method:

[0132] 1) Place the sample in a low temperature box.

[0133] 2) Set the test conditions: temperature cycle mode [-40 to 80°C] / 30 minutes / 150 cycles.

[0134] 3) After the thermal shock test, each specimen was subjected to tensile and leakage tests.

[0135] [Experimental Example 3]

[0136] <Tensile test after constant temperature and humidity exposure>

[0137] Test machine: SUKSAN SE-CT-02

[0138] Test method:

[0139] 1) Place the sample in a high temperature and high humidity chamber.

[0140] 2) Set the test conditions: temperature [80°C] / humidity [95%] / duration [200 hours].

[0141] 3) After the thermal shock test, each specimen was subjected to tensile and leakage tests.

[0142] Tensile testing, bond strength measurement based on elapsed time, and sealing testing were performed using the specimens from Conventional Examples 1-2, Inventive Examples 1 to 15, and Comparative Examples 1 to 7. The results are summarized in Table 5 below.

[0143] Table 5

[0144]

[0145]

[0146] The test results in each embodiment are as follows.

[0147] In Inventive Example 1, both the Ti and Al samples produced excellent results.

[0148] In Comparative Example 1, the tensile strength results of the Ti sample were poor, while the results of the Al sample were good. In Inventive Example 2, the tensile strength results of the Ti sample were good, while the results of the Al sample were excellent. In Inventive Example 3, the tensile strength results of the Ti sample were excellent, while the results of the Al sample were good. In Inventive Example 4, both the Ti and Al samples produced good results.

[0149] In Comparative Example 2, the tensile strength result of the Ti sample was poor, while the result of the Al sample was good.

[0150] In Comparative Example 3, the tensile strength result of the Ti sample was slightly poor, but the result of the Al sample was good.

[0151] In Comparative Example 4, the tensile strength result of the Ti sample was good, but the result of the Al sample was slightly poor.

[0152] In Comparative Example 5, the tensile strength result of the Ti sample was good, but the result of the Al sample was poor.

[0153] In Comparative Example 6, the tensile strength result of the Ti sample was slightly inferior, and the result of the Al sample was relatively inferior.

[0154] In Inventive Example 5, both the Ti and Al samples produced good results.

[0155] In Inventive Example 6, both the Ti and Al samples produced good results.

[0156] In Comparative Example 7, the tensile strength result of the Ti sample was poor, but the result of the Al sample was good.

[0157] In Inventive Example 7, both the Ti and Al samples produced good results.

[0158] In Inventive Example 8, both the Ti and Al samples produced excellent results.

[0159] In Inventive Example 9, both the Ti and Al samples produced excellent results.

[0160] In Inventive Example 10, the tensile strength result of the Ti sample was excellent, while the result of the Al sample was good.

[0161] In Inventive Example 11, both the Ti and Al samples produced good results.

[0162] In Inventive Example 12, both the Ti and Al samples produced good results.

[0163] In Inventive Example 13, both the Ti and Al samples produced good results.

[0164] In Inventive Example 14, both the Ti and Al samples produced good results.

[0165] In Inventive Example 15, both the Ti and Al samples produced excellent results.

[0166] The test results in the general example are as follows.

[0167] In Conventional Example 1, the tensile strength result of the Ti sample was poor, while the result of the Al sample was good.

[0168] In Conventional Example 2, the tensile strength result of the Ti sample was good, but the result of the Al sample was poor.

[0169] Compared with the Al sample prepared under the specific conditions of Al in Conventional Example 1, the test results of the Al and Ti samples prepared under the various conditions of the inventive examples show equivalent or better performance.

[0170] Compared with the Ti sample prepared under the specific conditions of Ti in Conventional Example 2, the test results of the Ti and Al samples prepared under the various conditions of the inventive examples show equivalent or better performance.

[0171] Industrial Applicability

[0172] The present invention relates to a method for preparing a combination of a polymer and Ti or Al, wherein the bonding strength between the polymer and Ti or Al is enhanced by surface treating Ti or Al under the same conditions, thereby improving the sealing performance of the component.

[0173] Description of Reference Numerals

[0174] 1.Ti or Al metal components

[0175] 2. Polymer building blocks

[0176] 3. Combination of polymer and Ti or Al

[0177] 10. Hole

[0178] 20. Injection gate.

Claims

1. A method for bonding a polymer and a metal by surface treating Ti and Al under the same conditions, which involves bonding a polymer to Ti or a polymer to Al, the method comprising: a degreasing step, in which a degreasing detergent is used to remove contaminants from the metal surface; A first etching step, wherein the metal surface is etched with an alkaline solution; a decontamination step, wherein contaminants are removed from the metal surface; an activation step, in which the metal surface is etched a second time with a strong acid solution; an anodizing step, wherein a porous structure is formed on the activated metal surface; and A drying step for drying the metal surface after anodizing treatment; The anodizing step is carried out at a temperature of 30-50°C and a temperature of 1.0-2.55A / dm 2 A mixed acidic solution with a pH of 4.5-5.5 is used for 300-1200 seconds at a current density of 1.5-2.0, wherein the mixed acidic solution includes one or more of sulfuric acid (concentration 1-3 g / L), phosphoric acid (concentration 2-7 g / L), chromic acid (concentration 1-5 g / L), oxalic acid (concentration 1-5 g / L) and hydrofluoric acid (concentration 0.5-2 g / L), and one or more of sodium sulfate (concentration 5-10 g / L), phosphate (concentration 1-5 g / L) and oxalate (concentration 1-3 g / L), and triazine thiol derivatives and salts thereof (concentration 0.01-0.10 g / L) are added as additives.

2. The method according to claim 1, wherein: In the anodizing step, the additive used is one of the following triazine thiol derivatives and their salts: 1,3,5-Triazine-2,4,6-trithiol (TT), 1,3,5-Triazine-2,4,6-trithiol monosodium salt (TTN), 1,3,5-Triazine-2,4,6-trithiol triethanolamine salt (F-TEA), 6-anilino-1,3,5-triazine-2,4-dithiol (AF), 6-anilino-1,3,5-triazine-2,4-dithiol monosodium salt (AFN), 6-Dibutylamino-1,3,5-triazine-2,4-dithiol (DB), 6-Dibutylamino-1,3,5-triazine-2,4-dithiol monosodium salt (DBN), 6-Diallylamino-1,3,5-triazine-2,4-dithiol (DA), 6-Diallylamino-1,3,5-triazine-2,4-dithiol monosodium salt (DAN), 1,3,5-Triazine-2,4,6-trithiol di(tetrabutylammonium) salt (F2A), 6-Dibutylamino-1,3,5-triazine-2,4-dithiol tetrabutylammonium salt (DBA), 6-Dioctyl-1,3,5-triazine-2,4-dithiol (DO), 6-Dioctyl-1,3,5-triazine-2,4-dithiol monosodium salt (DON), 6-Dilauroylamino-1,3,5-triazine-2,4-dithiol (DL), 6-Dilauroylamino-1,3,5-triazine-2,4-dithiol monosodium salt (DLN), 6-stearoylamino-1,3,5-triazine-2,4-dithiol (ST), 6-stearoylamino-1,3,5-triazine-2,4-dithiol monopotassium salt (STK), 6-oleoylamino-1,3,5-triazine-2,4-dithiol (DL), and 6-oleoylamino-1,3,5-triazine-2,4-dithiol monopotassium salt (OLK).

Citation Information

Patent Citations

  • JP1971000701Y1

  • Resin titanium metal joined body and method for manufacturing the same

    JP2019048407A